Neuropsychiatric systemic lupus erythematosus: association with global disease activity. (April 2014) - Morrison, E; Carpentier, S; Shaw, E; Doucette, S; Hanly, JG
Objective: To determine whether patients with neuropsychiatric (NP) events attributed to systemic lupus erythematosus (SLE) have more global disease activity than patients with NP events not attributed to SLE. Methods: Patients were recruited from an academic lupus clinic. Global disease activity was measured with the SLE Disease Activity Index 2000 (SLEDAI-2K) and organ damage with the Systemic Lupus International Collaborating Clinics (SLICC)/American College of Rheumatology (ACR) damage index (SDI). NP disease was defined using the ACR case definitions and decision rules for attribution of NP events to SLE and non-SLE causes. Results: There were 68 patients (age (mean ± SD) 40.8 ± 15.2 years, 85% female, 94% Caucasians) with 126 NP events. SLEDAI-2K scores in patients with NP events attributed to SLE were higher than in patients with NP events attributed to non-SLE causes even when NP variables were removed from the SLEDAI-2K (mean ± SD: SLE NP = 7.36 ± 5.42 vs non-SLE NP = 5.53 ± 4.57, P = 0.042). Patients with CNS and diffuse NP events, rather that PNS and focal events, accounted for the group differences in SLEDAI-2K scores. There were no significant differences in total SDI scores comparing NP events due to SLE vs. non-SLE causes (mean ± SD: 2.1 ± 1.8 vs. 1.7 ± 1.7; p = 0.28) even when NP variables were omitted. Conclusions: Increased global SLE disease activity is associated with concurrent NP events attributed to SLE, particularly for diffuse NP and CNS NP events. The findings have diagnostic and therapeutic implications for SLE patients with NP events and inform pathogenetic mechanisms underlying NPSLE.